THE MAIN CHARACTERISTICS OF THE PRESCHOOL EDUCATION SYSTEM IN THE WORLD - G'aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2023)
This article provides information on the specific features, goals and objectives of the system of preschool education in foreign countries (for example, the UK and Germany), their types and reforms in this system in our country.